Carbon Nanomaterials With Hollow Structures: A Mini-Review - Liu, Fan; Cheng, Yu; Tan, Junchao; Li, Jiantong; Cheng, Haoyan; Hu, Hao; Du, Chunya; Zhao, Shuang; Yan, Yan; Liu, Mingkai (Frontiers in Chemistry, 2021)
Carbon nanomaterials with high electrical conductivity, good chemical, and mechanical stability have attracted increasing attentions and shown wide applications in recent years. In particularly, hollow carbon nanomaterials, which possess ultrahigh specific surface area, large surface-to-volume ratios, and controllable pore size distribution, will benefit to provide abundant active sites, and mass loading vacancy, accelerate electron/ion transfer as well as contribute to the specific density of energy storage systems. In this mini-review, we summarize the recent progresses of hollow carbon nanomaterials by focusing on the synthesis approaches and corresponding nanostructures, including template-free and hard-template carbon hollow structures, metal organic framework-based hollow carbon structures, bowl-like and cage-like structures, as well as hollow fibers. The design and synthesis strategies of these hollow carbon nanomaterials have been systematically discussed. Finally, the emerging challenges and future prospective for developing advanced hollow carbon structures were outlined.